Germany after the grand coalition: governance and politics in a turbulent environment - Bolgherini, Silvia; Grotz, Florian (Europe in transition: the NYU European studies series, 2010)
Introduction : The grand coalition 2005-2009 - a single episode or a turning point? / Silvia Bolgherini and Florian Grotz -- New possibilities or permanent gridlock? The policies and politics of the grand coalition / Reimut Zohlnhöfer -- Toward a new German federalism? How the 2006 constitutional reform did (not) change the dynamics of the federal system / Julia von Blumenthal -- Multilevel party politics during the grand coalition : electoral outcomes at Länder level / Silvia Bolgherini and Florian Grotz -- Still the driving force of European integration? The EU policy pursued by the grand coalition / Gisela Müller-Brandeck-Bocquet -- A post-modern campaign? The sleepy development to the 2009 federal election / Giorgia Bulli -- The choice for stability : the results of the 2009 federal election / Mario Caciagli -- An electorate on the move : explaining vote choice in the 2009 federal election / Bernhard Wessels -- Coalition-building in Germany 2009 : simulating real politics, preparing Merkel III? / Suzanne S. Schüttemeyer -- A fresh state or more of the same? The domestic policy agenda of the center-right coalition / Roland Sturm -- The "grand coalition state" between past and present : continuities and discontinuities of a changing political system / Gabriele D'Ottavio -- Conclusion : The long shadow of the grand coalition / Florian Grotz and Silvia Bolgherini